Executable Music Documents - De Roure, D (Association for Computing Machinery, 2014)
While good practices are emerging with respect to publication of data alongside research outputs, we argue that computational descriptions (e.g. scripts, software and workflows) should also be included so that research can be interpreted, reconstructed and recomputed. A research article—or Research Object—should then describe all the components associated with a piece of digital research, including the descriptions of code and algorithms, effectively comprising an executable document. Furthermore we observe that such a re-executable object can be re-run automatically. The Music Information Retrieval research community has established community infrastructure and practices which are amenable to this approach, providing a glimpse of a future Music Digital Library. These ideas raise a number of issues for Digital Libraries more generally.